The Role of Education in Shaping Awareness and Attitudes Towards Politics - Beeranna; Nandana Gurappa Basappa (International Journal of Education Sciences, 2025)
Education provides individuals with a comprehensive understanding of the mechanisms of political systems, encompassing the functions of government, the intricacies of electoral processes, and the significance of political parties. The comprehension of the decision-making process is improved, and it demonstrates how people can actively influence those decisions. Education not only impacts people's political knowledge but also their attitudes toward politics and their sense of self as active citizens. In contrast to negative educational experiences, which may lead to apathy or indifference, positive educational experiences can foster constructive political attitudes. Additionally, education enables people to recognize biases in political discourse, critically analyze political narratives, and judge the reliability of information sources. Education prepares people to be informed voters and engaged participants in democratic processes by encouraging critical thinking and civic awareness. In order to facilitate inclusive discourse and representation, it also provides a forum for bridging socioeconomic and generational divides in political knowledge. Because they incorporate civic education into their curricula and promote dialogue on current political concerns, educational institutions are essential to this process. These initiatives play a key role in creating a politically aware society where people understand their rights and obligations as citizens. The purpose of this study was to analyze previous research in order to better understand how education influences people's political knowledge and sentiments.
Keywords: Awareness towards politics; democratic participation; education; electoral processes; politics